LA PROMOCIÓN EMPRESARIAL DE LA MICRO EMPRESA EN EL AA.HH. PUERTO PACHACúTEC DEL DISTRITO DE VENTANILLA, REGIÓN CALLAO - Bellido Salcedo, César Augusto (2013)
Today, Peru is experiencing a period of economic stability. In the last 12 years, the country has had especially solid and sustainable growth. However, growth should translate into development. While itis true that poverty has declined, a stratum of society should be encouraged and promoted to greatereconomic inclusion. Human settlements (HHSS), which are part of these social stratums, provide anopportunity to capture the generation of micro-enterprises as forms of formality and development.This project aims to analyze the generation of micro-businesses promotion in the in Puerto PachacutecHuman settlement, located in the district of Ventanilla in the Callao region. This project is framed ina field study, as an analysis of the current status and possibilities that may arise in the developmentof this human settlement.In the first stage of the project, a database has been developed of the number of traders who arecurrently exerting an economic activity in the area. A study has also been done (based on a samplingof the population) of the educational level, accessibility to public services, social media engagementand perception of the support received from the government, both on central and local levels. Finally,we will analyze the results and consider proposals for each of the variables presented, all of themfocused on the central theme of our study and to see results of the possible social impact.